The perfectly motivated nurse and the others: workplace and personal characteristics impact preference of nursing tasks - Koch, Sven H.; Proynova, Rumyana; Paech, Barbara; Wetter, Thomas (Journal of nursing management, 2014)
Aims: To identify whether motivation of nurses coincides with personal values, workplace or personal characteristics. Background: Shortage of nursing workforce compromises patient care. Motivation and job satisfaction are factors considered to make nurses quit. Little is known about measurement and variation of nurses' motivation. Funding for human resource programmes is limited - effective programmes could focus on nurses in need of motivational support. Methods: Exploratory study with nurses using questionnaires in an academic hospital in Germany. Work motivation was approximated through preference of nursing tasks. Questionnaires measured personal values, preference of generic nursing tasks, and workplace and personal characteristics. Results: A total of 212 questionnaires were usable. Higher motivation was found in groups of nurses with the dominant personal value ‘Benevolence’, with high self-rated expertise, in the middle of their career or working in surgical or general wards. Motivation was low in nurses with the dominant value ‘Hedonism’, or nurses in internal medicine or with low to medium self-rated expertise or who used computers infrequently. Conclusions: Motivation coincided with dominant personal values, workplace and personal characteristics. The results should be validated in other settings. Implications for nursing management Human resource programmes could focus on nurses whose motivation is at risk. Prospectively highly motivated individuals should be hired with priority.
Gesehen am 22.09.2020